Upaya Meningkatkan Perkembangan Moral Dan Agama Melalui Pembiasaan Hafalan Doa Doa Dengan Metode Talaqqi di Madin Azzahro Prajegan Sukorejo - Rokhmah Purwanti; Ahmad Syafi'i Sulaiman Jamrozi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The formation of the Banom or IPNU IPPNU organization in Bekiring village, Pulung sub-district, Ponorogo, already has one of the programs, Al-Quran khotaman. This research describes the habituation of religious activities in forming religious characters. The service method used is Asset Based Community Development (ABCD). Data collection techniques include observation, interviews, and documentation. Because character education is a behavioral education formed through habitual action or habits and exemplary, habituation must be done to form the character. With the Khotaman Al-Qur'an activity, it is hoped that it will be able to provide understanding to youth and the community in Bekiring Village, Pulung District, to continue reading the Koran and be able to strengthen faith. The program is to make khotamil Qur'an activities a medium of da'wah which aims to deepen religious knowledge and also to strengthen the IPNU IPPNU membership forum in Bekiring village, Pulung sub-district.